Developing an Ethnoscience-Based AKM instrument: Evidence of Content Validity and Item Quality - Sukmaningrum Latifah Oktaviani; Sri Yamtinah; Budi Hastuti (PAEDAGOGIA, 2026)
This study uses a descriptive quantitative approach that aims to describe and analyze the quality of Minimum Competency Assessment (AKM) questions developed in integrated ethnoscience learning with a focus on scientific literacy and numeracy literacy in the topic of salt hydrolysis. There are various question formats, namely multiple choice, complex multiple choice, matching, short answer (fill in the blank), and true-false. The item quality analysis in this study involved: difficulty level testing, discrimination power testing, and instrument reliability testing. The difficulty level testing was conducted to determine the proportion of students who were able to answer each item correctly. The discrimination power testing aimed to determine the ability of each item to distinguish between high-ability and low-ability students. Meanwhile, the reliability testing was conducted to assess the overall internal consistency of the test instrument in measuring students' scientific literacy and numeracy skills.The variety of question formats is designed to accommodate the characteristics of AKM which emphasizes higher-order thinking skills, conceptual understanding, and the application of knowledge in the context of everyday life based on ethnoscience.The analysis results show that the majority of test items fall into the moderate difficulty category, indicating that they are neither too easy nor too difficult for students. Furthermore, the discriminatory power of the test items is in the good category, meaning each item effectively differentiates students with different ability levels. High instrument reliability indicates that the test instrument has good consistency and can provide stable and reliable measurement results.